Trade-offs between wood supply and caribou habitat in northwestern Ontario - McKenney, Daniel; Nippers, Bryan; Racey, Gerald; Davis, Rob (Rangifer, 1998)
Woodland caribou habitat management in northwestern Ontario is a complex spatial problem. The Strategic Forest Management Model (SFMM), a linear programming PC-based planning tool being developed in Ontario, was used to examine the impacts of alternative management strategies on caribou habitat. The management alternatives investigated included the cessation of timber management and maximising the present value of wood production without any explicit concern (in the model) for caribou. Three major findings are worth noting: 1) trying to maintain prime caribou habitat within active Forest Management Units will come at a cost to wood supply but the cost will depend on the absolute amount of area affected and the spatial configuration of that land in relation to mills. The cost of maintaining caribou habitat in one management unit at a level about 25 000 hectares is roughly 324 000 per year (about 3 cents for each Ontario resident). The imposition of an even-flow constraint on wood production is in fact potentially more costly; 2) Given the region is heavily dominated by spruce aged 90 years and over, forest succession and fire disturbance will likely cause large declines in prime caribou habitat in the near to medium term (20 to 40 years) even if no timber harvesting occurs; 3) The complexities of the trade-offs in this resource management problem highlight the limitations of any single modelling tool to satisfactorily address all issues. Planners need to take advantage of a wide range of analytical techniques to quantify the issues and formulate integrated policies.